2020
DOI: 10.4038/jfa.v13i1.5225
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Physicochemical Properties and Proximate Composition of Improved and Traditional Varieties of Rice in Sri Lanka

Abstract: Sri Lankan traditional rice varieties (SLTRV) have been known to be associated with higher nutritional and healthcare properties but along with the rice market, cultivation of improved rice varieties is highly dominated at present. Therefore, this comparative study was done to investigate physicochemical parameters and proximate composition of selected traditional and improved rice varieties grown in Sri Lanka. Thirty-nine rice varieties including traditional and improved were cultivated and harvested at Rice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…AC of Bg 450, Bg 352 reported by Wickramasinghe and Noda (2008) are comparable with the values obtained in this study. The recorded AC of At 311 shows some deviations (lower values) compared to the values found in the literature (Hafeel et al 2020), for 2021/22 Maha and 2022 Yala seasons. According to the Hafeel et al, (2020), reported AC for improved varieties of Bg 360 and At 362, which are similar to that of the present study.…”
Section: Amylose Content (Ac)contrasting
confidence: 66%
See 2 more Smart Citations
“…AC of Bg 450, Bg 352 reported by Wickramasinghe and Noda (2008) are comparable with the values obtained in this study. The recorded AC of At 311 shows some deviations (lower values) compared to the values found in the literature (Hafeel et al 2020), for 2021/22 Maha and 2022 Yala seasons. According to the Hafeel et al, (2020), reported AC for improved varieties of Bg 360 and At 362, which are similar to that of the present study.…”
Section: Amylose Content (Ac)contrasting
confidence: 66%
“…With the technological developments, improved rice varieties were introduced in Sri Lanka by using bred adapting standard breeding techniques (Hafeel et al 2020). The high yielding improved rice varieties with resistance to pests and diseases and acceptable grain quality are currently cultivating throughout the Island, developed by the Department of Agriculture, Sri Lanka (Honge et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein content of the rice cracker is 6.82% and it is significantly higher when compared with the crackers incorporated with C. urens flour. According to Hafeel et al (2020), rice contains nearly 5%-9% protein, which is higher compared with that of C. urens flour (0.97%-Table 3). As rice flour contains higher protein compared with C. urens flour, when the level of incorporation of C. urens flour into crackers, the level of the protein content of the crackers is reduced.…”
Section: Nutritional and Functional Properties Of The Crackersmentioning
confidence: 99%
“…Preference for rice is mostly dependent on the color of the rice grain. Most of the traditional varieties have red pigment in the pericarp (rice bran) except few white pericarp rice varieties such as Suwandel, Gonabaru, Suduru Samba, Iginimittiya, Rathal, and Dular (Rebeira et al, 2014;Hettiarachchi et al, 2016;Abeysekera et al, 2017a;2017b;Hafeel et al, 2020), but most of the improved rice varieties have white pericarp (Hettiarachchi et al, 2016;Hafeel et al, 2020). Traditional rice is generally but partially polished to retain the red pigment on the grain whereas white pericarp rice is purposely and completely polished for better appearance.…”
Section: Grain Quality Characteristicsmentioning
confidence: 99%